2004
DOI: 10.1002/vnl.20014
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphite transformations in flexible PVC formulations

Abstract: Organophosphites are a versatile component of liquid PVC heat stabilizers and stabilize PVC through a variety of mechanisms. Organophosphites can decompose peroxides, replace labile chlorines on the PVC backbone, scavenge HCl (via the Arbuzov rearrangement), complex Lewis acids, and add to double bonds. This paper attempts to identify the relative contributions of these mechanisms in both model systems and flexible PVC formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…These studies were more recently confirmed by Jakupca et al 56 who studied oxidation of paraffins at 180 o C in the presence of triphenyl and tri-n-octyl phosphites. Alkyl phosphite was more reactive towards peroxides than aryl phosphite.…”
Section: Reactions With Isolated Unsaturationssupporting
confidence: 57%
See 4 more Smart Citations
“…These studies were more recently confirmed by Jakupca et al 56 who studied oxidation of paraffins at 180 o C in the presence of triphenyl and tri-n-octyl phosphites. Alkyl phosphite was more reactive towards peroxides than aryl phosphite.…”
Section: Reactions With Isolated Unsaturationssupporting
confidence: 57%
“…Alkyl phosphite was more reactive towards peroxides than aryl phosphite. 56 It should be noted that although alkyl phosphites are more reactive than aryl phosphites, they are also less hydrolytically stable. 56 Triphenyl phosphite was also converted into triphenyl phosphate, but at a much slower rate compared to alkyl phosphite.…”
Section: Reactions With Isolated Unsaturationsmentioning
confidence: 99%
See 3 more Smart Citations